Evidence-Based Approach to Timing of Nerve Surgery: A Review. Issue 3 (September 2021) - MacKay, Brendan J.; Cox, Cameron T.; Valerio, Ian L.; Greenberg, Jeffrey A.; Buncke, Gregory M.; Evans, Peter J.; Mercer, Deana M.; McKee, Desirae M.; Ducic, Ivica
Abstract: Events causing acute stress to the health care system, such as the COVID-19 pandemic, place clinical decisions under increased scrutiny. The priority and timing of surgical procedures are critically evaluated under these conditions, yet the optimal timing of procedures is a key consideration in any clinical setting. There is currently no single article consolidating a large body of current evidence on timing of nerve surgery. MEDLINE and EMBASE databases were systematically reviewed for clinical data on nerve repair and reconstruction to define the current understanding of timing and other factors affecting outcomes. Special attention was given to sensory, mixed/motor, nerve compression syndromes, and nerve pain. The data presented in this review may assist surgeons in making sound, evidence-based clinical decisions regarding timing of nerve surgery.